2015
DOI: 10.3389/fvets.2015.00028
|View full text |Cite
|
Sign up to set email alerts
|

An Introduction to the Avian Gut Microbiota and the Effects of Yeast-Based Prebiotic-Type Compounds as Potential Feed Additives

Abstract: The poultry industry has been searching for a replacement for antibiotic growth promoters in poultry feed as public concerns over the use of antibiotics and the appearance of antibiotic resistance has become more intense. An ideal replacement would be feed amendments that could eliminate pathogens and disease while retaining economic value via improvements on body weight and feed conversion ratios. Establishing a healthy gut microbiota can have a positive impact on growth and development of both body weight an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
91
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(94 citation statements)
references
References 248 publications
2
91
0
1
Order By: Relevance
“…Gao et al (2008) reported that growth performance and immune modulatory functions improved in broilers fed with yeast product. It has been shown that yeast product contains beneficial nutrients such as peptides, oligosaccharides, flavors and aroma substances which increase nutrient digestibility, enhance the growth of beneficial bacteria such as Lactobacillus and improve gut immunity against pathogens (Roto et al, 2015). Adil et al (2010) supplemented broiler diets with various levels of different organic acids to evaluate the effects of acidifiers on productive performance and gut morphology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gao et al (2008) reported that growth performance and immune modulatory functions improved in broilers fed with yeast product. It has been shown that yeast product contains beneficial nutrients such as peptides, oligosaccharides, flavors and aroma substances which increase nutrient digestibility, enhance the growth of beneficial bacteria such as Lactobacillus and improve gut immunity against pathogens (Roto et al, 2015). Adil et al (2010) supplemented broiler diets with various levels of different organic acids to evaluate the effects of acidifiers on productive performance and gut morphology.…”
Section: Discussionmentioning
confidence: 99%
“…The beneficial effects of yeast, whey and acidifiers as growth promoters and immune enhancers have already been demonstrated (Gao et al, 2008;Szczurek et al, 2013;Ricke, 2003). For example, yeast product, which contains high amounts of mannan chains (Roto et al, 2015), is a basic component of some commercially available prebiotics and has been shown to improve body weight gain, feed conversion ratio and immune response in broilers (Gao et al, 2008). Whey, another known additive that is a source of different nutrients such as proteins and carbohydrates (Szczurek et al, 2013) is also a source of lactose.…”
Section: Introductionmentioning
confidence: 99%
“…They are mainly carbohydrates that are indigestible to the host, are selectively fermented by beneficial microbiota in the gut, so as to provide energy to promote bacterial growth and metabolism in the colon. These contribute to specific changes that lead to improved host health (Roto et al, 2015;Maynard et al, 2012). Prebiotics act under different mechanisms, whose depends on the nature of the compound.…”
Section: Introductionmentioning
confidence: 99%
“…Sc is used as a feed additive in avian production because it is a rich source of protein, fiber, and minerals, provides essential B vitamins (biotin, niacin, pantothenic acid and thiamin and its biological value is high) and organic acids (Adebiyi et al, 2012;Roto et al, 2015), resulted in increased growth and improved health in broilers (Miazzo et al, 2001(Miazzo et al, , 2010Zang et al, 2005;Hosseini, 2011;Adebiyi et al, 2012;Roto et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation